Nutraceuticals and dietary supplements : applications in health improvement and disease management - Keservani, Raj K.; Sharma, Anil K.; Kesharwani, Rajesh Kumar (Canada, 2021)
"Addressing the increasing popularity of nutraceuticals, dietary supplements, and functional foods, this comprehensive and timely book presents an abundance of information on herbal products and their applications. The chapter authors-highly skilled, experienced, and renowned scientists and researchers from around the globe-offer up-to-date knowledge on the uses of herbal products in health management, in cancer treatment, in mental health therapy, and more. Nutraceuticals and Dietary Supplements: Applications in Health Improvement and Disease Management begins with an introduction, the nomenclature, and characteristics of nutraceuticals and goes on to discuss in-depth applications for specific health issues, including cancer, diabetes, Alzheimer's disease, alcoholism, and more. It also looks at the pros and cons as well as the analytical techniques used for the production of nutraceuticals. Chapters cover market size, regulatory perspectives, manufacturing, and in silico drug design. The book incorporates a wide diversity of case studies, research, and theories pertaining to natural products employed by developers and content experts in the field. This essential reference builds on the available literature in the field of pharmacy and biological sciences and will be a welcome resource for scientists, researchers, and pharmaceutical industry professionals"--
Includes bibliographical references and index.
Keywords: Functional food; Dietary supplements